Diagnosis of Arachnoid Cysts on Prenatal Ultrasound - Koç, Mustafa; Kırış, Adem; Akbaş, Gökhan (Fırat University, 2007)
Arachnoid cysts constitute 1% of all intracranial mass lesions. Arachnoid cysts are benign congenital anomalies caused by accumulation of cerebrospinal fluid in cystic structures formed within two layers of arachnoid membranes. The aetiopathogenic and physiopathological mechanisms of arachnoid cysts are a source of controversy. In most of the cases radiologic imaging has in valuable. It is difficult to diagnosis in utero with ultrasonography. Pre-diagnosis is very important in terms of the prevention of the future deformation. We report a case where fetal cerebral ultrasonography shows an extraventricular cystic formation of liquid appearance, after 32 weeks of pregnancy. ©2007, Firat University, Medical Faculty

Araknoid kistler intrakraniyal kitlelerin yaklaşık %1'ini oluşturan, araknoid tabaka ile devamlılık gösteren, sıklıkla ekstraaksiyel bölgede dura ile beyin arasında yerleşen benign lezyonlardır. Etyopatojenik ve fizyopatolojik mekanizmaları günümüze kadar tam olarak aydınlatılamamıştır. Radyolojik görüntüleme olguların çoğunda tanısal değer taşımaktadır. Ultrasonografi (US) ile in utero teşhis edilmeleri zordur. Olguların erken tanınması ileride gelişebilecek nörolojik sekellerin önlenmesi açısından oldukça değerlidir. Biz bu olgumuzda 32 haftalık gebede fetüste serebral ekstraventriküler yerleşimli araknoid kistin US bulgularını tanımladık. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Araknoid Kist Olgusu: Prenatal Ultrasonografi Bulguları